The Overview of Smoking on Clotting Time Results Among Students of Politeknik Piksi Ganesha - Sudrajat, Agus; Alwi , Ryo Gerald Valentio (Science Tech Group, 2024)
The World Health Organization (WHO) in 2019 stated that smoking is one of the biggest challenges in global health, as it causes approximately 6 million deaths worldwide each year. One of the effects of smoking is an increase in plasma homocysteine levels. This study is an analytical study with a cross-sectional design using quota sampling technique. The research sample consisted of students from Politeknik Piksi Ganesha aged 20-25 years who were active smokers. The study used the Lee-White method to measure blood clotting time. According to the results, it can be concluded that the blood clotting time among smoking students at Politeknik Piksi Ganesha tends to be shorter, with 18 out of 30 samples (60%) showing a shortened clotting time, while the remaining 12 samples (40%) exhibited normal clotting times. This study emphasizes that smoking is a major factor that can affect the body's hemostatic system, potentially leading to prolonged clotting time.